Pengaruh kedalaman dan lama menyelam terhadap ambang-dengar penyelam tradisional dengan barotrauma telinga - Arief Tjatur Prasetyo; Joseph Bambang Soemantri; Lukmantya Lukmantya (PERHATI-KL, 2012)
Background: Ear barotrauma is ear tissue damage resulted by the inability to equalize pressure in the middle ear space with the ambient pressure. The greatest relative change in pressure during diving,is near the surface. Ear barotrauma can occur when diving done without equalizing middle ear pressurewith proper procedures. Recurrent ear barotrauma in a long time period can use damage of elastic fibersrecoiling capacity of the tympanic membrane to be irreversible, so it can cause hearing loss. Suddenpressure changes in middle ear space, can be forwarded to the inner ear so it can cause inner eardamage, even deafness. Purpose: This study aims to determine the effect of depth and diving durationto hearing threshold in the traditional divers (divers with diving air compressor tools), who experienced ear barotrauma, and to know the incidence of ear barotrauma. Method: This was an observational analytic study with cross sectional data collection. Data analysis used the cross table, ChiSquare(X2), Spearman correlation and logistic regression test. Result: On October 8 - December 18, 2011 has been conducted a study in traditional divers. 24 samples from 74 population were found. 50 persons with noear barotrauma founds no significant statistic differences with characteristic samples. The results ofChi - Square and Spearman correlationthe showed p=0.350, p=0.382 and p=0.372, p=0.281, which are>a(0.05). The result of logistic regression test showed significancy values were 0.771 and 0.610, whichwere >a(0.05). Ear barotrauma incidence is 32.4%. Conclusion: There is no significant effect of depthand duration of diving to hearing threshold in the traditional divers who experienced ear barotrauma.Ear barotrauma incidence is 32.4%. Keywords: ear barotrauma, diving depth, diving duration, hearing threshold. Abstrak : Latar belakang: Barotrauma telinga adalah kerusakan jaringan telinga akibat ketidak-mampuanmenyamakan tekanan ruang telinga tengah dengan lingkungan. Perubahan tekanan relatif terbesar selamamenyelam terdapat di dekat permukaan. Barotrauma telinga dapat terjadi apabila penyelaman tanpamelaksanakan ekualisasi tekanan telinga tengah dengan cara yang benar. Barotrauma telinga berulangdalam periode lama dapat menyebabkan gangguan kapasitas recoiling serabut elastis membran timpanimenjadi irreversible, sehingga dapat menyebabkan gangguan pendengaran. Perubahan tekanan mendadakdi ruang telinga tengah dapat diteruskan ke telinga dalam sehingga dapat menyebabkan kerusakan telingadalam, bahkan ketulian. Tujuan: Mengetahui pengaruh kedalaman dan lama menyelam terhadap perubahanpendengaran pada penyelam tradisional (penyelam dengan alat bantu selam kompresor udara) yangmengalami barotrauma telinga, serta angka kejadian barotrauma telinga. Metode: Merupakan penelitianobservasional analitik, dengan pengambilan data secara cross sectional. Analisis data menggunakan tabelsilang, uji Chi-Square (X), korelasi Spearman dan regresi logistik. Hasil: Pada Oktober - Desember 2011telah dilakukan penelitian pada penyelam tradisional. Didapatkan 24 sampel dari 74 populasi. Terdapat50 orang tidak mengalami barotrauma telinga, yang tidak terdapat perbedaan statistik signifikan dengankarakteristik sampel. Hasil uji Chi-Square dan korelasi Spearman menunjukkan nilai p=0,350, p=0,382, danp=0,372, p=0,281, yang >a(0,05). Uji regresi logistik menunjukan nilai signifikansi 0,771 dan 0,610, yang>a(0,05). Angka kejadian barotrauma telinga sebesar 32,4%. Kesimpulan: Tidak terdapat pengaruh yangsignifikan kedalaman dan lama menyelam terhadap perubahan pendengaran pada penyelam tradisionalyang mengalami barotrauma telinga. Angka kejadian barotrauma telinga sebesar 32,4%.2 Kata kunci: barotrauma telinga, kedalaman menyelam, lama menyelam, ambang dengar